Long-term treatment of multiple sclerosis with azathioprine. Issue 1 (February 1973) - Swinburn, W. R.; Liversedge, L. A.
Abstract : Nineteen patients with multiple sclerosis were treated with azathioprine for two years. There was no evidence that treatment prevented deterioration or reduced the number or severity of the relapses when compared with 24 control patients observed over the same period.